MEASUREMENTS OF THE CHARACTERISTICS OF AN ELECTRIC MOTOR FOR AN ELECTRIC VEHICLE`S DRIVE - Srpčič, Klemen; Srpčič, Gregor (Journal of Energy Technology, 2023)
This paper aims to present the performance and measurement results of a load test performed on a brushless DC motor built into the wheel of a solar-powered vehicle. A brushless DC motor’s theoretical background and operation are presented at the beginning of the paper. The article covers the technical specification of the solar-powered vehicle and the inbuilt brushless DC motor. The measurements were performed with the described equipment at the Institute of Energy Technology, Faculty of Energy Technology, University of Maribor. Due to the unique design of the measured electric motor, it was also necessary to make a special housing, which was intended for connecting the electric motor to the test bench. The article concludes with an analysis of the measurement results in comparison with the data provided by the electric motor manufacturer.